2017
DOI: 10.1111/acer.13340
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Counterfeit Alcohol Purchases in Russia

Abstract: The literature has overestimated the impact of low prices on counterfeit alcohol consumption. Problem drinking and membership in social networks of consumers of surrogate alcohol (i.e., nonbeverage) are more influential in explaining why people purchase counterfeit alcohol. Further research on these 2 factors is needed to more fully understand the purchase and consumption of counterfeit alcoholic beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 34 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Research in Russia suggests that the Internet has become an important trade channel of counterfeits 1214 with the observed online sellers apparently operating as an intermediate link in the distribution chain of counterfeit alcohol in Russia, meeting the consumer’s stable demand for cheap alcohol. Therefore, measures against counterfeiting of alcohol should be part of specific policies to reduce unrecorded alcohol consumption and alcohol-related harms in Russia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Russia suggests that the Internet has become an important trade channel of counterfeits 1214 with the observed online sellers apparently operating as an intermediate link in the distribution chain of counterfeit alcohol in Russia, meeting the consumer’s stable demand for cheap alcohol. Therefore, measures against counterfeiting of alcohol should be part of specific policies to reduce unrecorded alcohol consumption and alcohol-related harms in Russia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Russia have focused on the consumption of alcohol surrogates 59 or homemade alcohol 6, 10, 11 , but comparatively little research has been done on other forms of unrecorded products, such as counterfeit alcohol 12, 13 . In the course of an ongoing longitudinal study on unrecorded alcohol consumption in Western Siberia 14 , we have observed various internet sellers of counterfeit spirits, ranging from individual offers on social networks and micro-blogs to specialized online shops offering forged expensive spirits brands.…”
Section: Unrecorded Consumption In Russiamentioning
confidence: 99%
“…Consequently, the objective characteristics of the Irkutsk tragedy include: regional scope (spatial locality), a high number of victims, high social significance (the real cause of surrogate alcohol consumption is the poverty of population, as was shown (Kotelnikova 2017)) and the prevalence of the problem.…”
Section: What Happened?mentioning
confidence: 99%
“…As shown by (Kotelnikova 2017) , the real cause of surrogate alcohol poisoning in Russia is poverty: people cannot afford quality alcohol and purchase surrogates instead. These topics are closely intertwined only in regional press.…”
Section: Constructing Problem Perception Through Connection With Othementioning
confidence: 99%
“…Statistical research has shown that liver cirrhosis prevalence may be explained by differences in patterns of drinking alone [21]. One confounding factor may be the preference of unrecorded alcohol consumption by people of lower socioeconomic status [22]. However, based on the typical low sample sizes in previous chemical studies on unrecorded alcohol, the hypothesis that compounds other than ethanol may contribute to the health risks of unrecorded alcohol is worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%